Breaking barriers: NEK2 inhibition shines in multiple myeloma treatment - Lischer, Christopher; Bruns, Heiko (Cell Reports Medicine, 2023)
In their article, Cheng et al.1 reveal that NEK2 loss reshapes the tumor microenvironment, reducing tumor-associated macrophages and decreasing T cell exhaustion. They show that this ultimately favors the immune system's anti-cancer response in multiple myeloma.
CRIS-Team Scopus Importer:2023-10-20